Insights on Intellectual Property Rights: Determination of Strategic Managment Strategies - Valliappan Raju, Assoc. Prof. Dr.; Siew Poh Phung, Dr. (International Journal of Engineering and Technology, 2019)
As of recent days in December 2018, the essential locus of significant worth for some, partnerships has been found in their licensed innovation rights. By one educated gauge from the late 1990s, some seventy five percent of the Fortune 100's aggregate market capitalization was spoken by immaterial resources, for example, licenses, copyrights and trademarks. In this Environment, IP the board can't be left to innovation chiefs or corporate legitimate staff alone. Given that the age of profits from IP rights is a capital-Ââ€escalated, long haul action and that choices influencing protected innovation are usually irreversible with ease, IP the executives must involve worry for useful and specialty unit pioneers and additionally an enterprise's most senior officers. Little of the composition regarding the matter of licensed innovation rights, nonetheless, has been coordinated at best dimension officials; rather it has every now and again been finished by masters, for pros. This paper has strived to determine some of the strategic management strategies that are worth embracing to ensure that the goals and objectives of the principle of intellectual property rights are achieved. Form the findings, it is evident that regular feedback provision and the decision by senior executives to embrace both top-down and bottom-up communication strategies constitute key approaches through which the mission and vision of the aspect of intellectual property rights could be achieved. Â